2021
DOI: 10.3390/microorganisms9020449
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Molecular Epidemiology and Laboratory Surveillance of Vaccine Preventable Bacterial Meningitis Agents: Streptococcus pneumoniae, Neisseria meningitidis, Haemophilus influenzae and Streptococcus agalactiae

Abstract: This narrative review describes the public health importance of four most common bacterial meningitis agents, Streptococcus pneumoniae, Neisseria meningitidis, Haemophilus influenzae, and S. agalactiae (group B Streptococcus). Three of them are strict human pathogens that normally colonize the nasopharynx and may invade the blood stream to cause systemic infections and meningitis. S. agalactiae colonizes the genito-gastrointestinal tract and is an important meningitis agent in newborns, but also causes invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 145 publications
(208 reference statements)
0
9
0
Order By: Relevance
“…However, immune pressure and selection against these pathogens can be expected to change their natural habitat and serogroups in the post-vaccine period. Thus, the ecology of GBS may make the effects of polysaccharide-conjugate vaccines on epidemiology challenging to predict [ 64 ]. In this study, our findings suggested that Rad-GBS could activate sufficient adaptive immune responses, likely CD4 + T cell-dependent and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, immune pressure and selection against these pathogens can be expected to change their natural habitat and serogroups in the post-vaccine period. Thus, the ecology of GBS may make the effects of polysaccharide-conjugate vaccines on epidemiology challenging to predict [ 64 ]. In this study, our findings suggested that Rad-GBS could activate sufficient adaptive immune responses, likely CD4 + T cell-dependent and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that, in time, resources will improve for these laboratories and they can submit a higher proportion of completely correct results, to increase their value to surveillance. This is an important aspiration, as NTHi and serotype a, e and f Hi strains and Nm serogroup W and Y strains do cause a significant amount of invasive disease [27][28][29][30]. Serotype replacement following Sp vaccination will also increase the need to broaden Sp serotyping [31].…”
Section: Identification and Typing Of Live Culturesmentioning
confidence: 99%
“…Streptococcus pneumoniae , Haemophilus influenzae , Neisseria meningitidis , Staphylococcus aureus , Klebsiella pneumoniae and Pseudomonas aeruginosa are among the bacterial pathogens that colonize the human upper respiratory tract (URT) [ 1 , 2 , 3 ]. Their pathogenicity is mediated by some major virulence factors involved in host cell adherence and invasion, tissue damage and immune evasion [ 4 , 5 , 6 , 7 ]. Despite being pathogenic, most individuals do not show any symptoms when these bacteria colonize the URT.…”
Section: Introductionmentioning
confidence: 99%